Alteration of plant species mixtures by virus infection: Managed pastures the forgotten dimension. (8th May 2022) - Jones, Roger A. C.
Abstract: What occurs when virus infection is spreading within a mixed plant species population? This question is important not only for economically significant, mixed species managed systems but also for environmentally significant mixed wild species populations. It received attention in recently published ecological studies on wild plant species, but these, and recent general pasture research publications, rarely mention earlier virus studies involving mixed species managed pasture. This review seeks to rectify that situation. It describes 10 diverse examples of past research on mixed species managed pasture done over two decades on three continents that demonstrated plant species balance changes arising from virus infection. These examples showed that plants belonging to susceptible pasture cultivars sensitive to systemic virus infection are sufficiently weakened that their ability to withstand competition from nonhost plants of other pasture species, or weed species, was diminished sufficiently to alter the plant species balance. Also, a similar alteration occurred when they were competing with virus‐resistant or virus‐tolerant host plants of the same or other pasture species, or a virus‐resistant weed species. Such competition also diminished seed production, which decreased their ability to regenerate. Notably, as reported subsequently with wild plant species populations, when two different pasture species infected by the same virus compete with each other, growth of the more sensitive species is suppressed. Because managed mixed species pastures constitute an important component of regenerative agriculture, retaining an optimal balance of pasture species and delaying pasture decline from weed invasion both require effective management of virus diseases. Abstract : This review seeks to highlight the major contribution made by past studies in managed pasture towards understanding the impacts of virus infection on the species balance in mixed plant species systems.